Postural deficiencies prevalence and correlation with foot conditions, body composition, and coordination, in Romanian preadolescents children: descriptive observational study - Vlad, Silviu; Ciobanu, Doriana I.; Fulop, Julia; Matei, Nicola; Cristea, Dana I.; Szabo-Alexi, Mariana; Blaga, Florin N.; Ianc, Dorina; Ilies, Alexandru B. (Frontiers in Pediatrics, 2025)
BackgroundCorrect posture during preadolescence is crucial for harmonious physical development and long-term musculoskeletal health. The examination of spinal and lower limb deficiencies in this age group represents a highly relevant and underexplored topic.ObjectiveTo determine the prevalence of postural deficiencies among Romanian preadolescents and to assess their correlations with body composition, coordination, and foot morphology.MethodsA total of 983 children aged 8–12 years (507 boys, 51.6%; 476 girls, 48.4%) were recruited from six middle schools in Oradea, Bihor County, Romania. Postural assessment followed Kendall et al.'s protocol using a plumb line and grid chart. Plantar pressure and center of gravity displacement were evaluated through baropodometry, while general coordination was assessed using the Matorin test.ResultsForward head posture was the most prevalent deficiency (641/983, 65.2%). Boys exhibited a higher prevalence of kyphosis (n = 448, 52.3%) compared with girls (n = 368,40.4%), while scoliosis occurred more frequent in girls (n = 306, 33.6%) vs. (n = 257, 26.1%). Significant correlations were observed between ankle valgus and scoliosis [x2(1) = 7.87, p = .005], flatfoot and scoliosis [x2(1) = 7.87, p = .005], and flatfoot and coordination deficits [x2(3) = 22.96, p = .005].ConclusionsForward head posture emerged as the most common spinal deficiency. Notable associations were identified between body composition and kyphosis, hyperlordosis, and ankle valgus, as well as between flatfoot, scoliosis, and impaired coordination. These findings underscore the importance of early detection and the implementation of targeted prevention programs to address postural deficiencies during childhood.